Review Nutritional interventions during adolescence and their possible effects - Soliman, Ashraf T; Alaaraj, Nada; Noor Hamed ,; Alyafei , Fawzia; Ahmed , Shaymaa; Shaat , Mona; Itani, Maya; Elalaily, Rania; Soliman, Nada (Acta Biomedica Atenei Parmensis, 2022)
Nutrition is one of the most important factors affecting pubertal development. Increasing demands for energy proteins and micronutrients are necessary to cope with the rapid linear pubertal growth and development, change in body composition, and increased physical activity. Adequate nutrition is a key permissive factor for the normal timing and tempo of pubertal development. Severe primary or secondary malnutrition also can adversely delay the onset and progression of puberty. The higher incidence of anorexia nervosa and bulimia in adolescents imposes a nutritional risk on pubertal development. Here we provide an overview of nutritional requirements (macronutrients and micronutrients) necessary to cope with these changes. In addition, we discuss possible nutritional interventions trials and their effects on several aspects of growth and development in undernourished and stunted adolescents, in low- and middle-income countries (LMIC), who require nutritional rehabilitation. This mini-review sums up some important findings in this important complex that links between nutrition, nutritional interventions, and pubertal development